Loan pricing and biodiversity exposure: Nature-related spillovers to the financial sector - Annette Becker; Francesca Erica Di Girolamo; Caterina Rho (European Commission, 2023)
Biodiversity loss can have direct economic impacts, as it limits the availability of natural resources and increases costs across various industries. When firms face significant risks due to biodiversity loss, their creditworthiness may be jeopardized. This raises concerns for lending institutions that have provided credit to these companies, potentially leading to stricter lending conditions for borrowers. This paper analyzes how these risks spread from the real economy to the syndicated loans market in the European Union and United Kingdom. Firstly, we construct a country-level indicator of biodiversity exposure for EU lenders. Our findings show that the exposure of EU banks to biodiversity varies across countries, depending on the level of exposure of borrowing firms and the loan volumes. Secondly, using data on syndicated loans from 2017 to 2022, we observe a positive and significant correlation between loan pricing and the level of biodiversity exposure of the borrower. These findings suggest that creditors are increasingly incorporating nature-related information into their financing decisions, allowing them to diversify and pool risks. On the other hand, debtors cannot fully detach themselves from their dependence on natural capital and can only adjust their business models in the long run.
Keywords: C55; G21; Q51; Q57; 330; Nature-related risk; Natural capital; Biodiversity; Financial sector; Banks; Debt financing; Syndicated loans; Loan pricing; Premium; International spillovers; Risk transmission; Borrower diversification; EU